2015 IEEE International Instrumentation and Measurement Technology Conference (I2MTC) Proceedings 2015
DOI: 10.1109/i2mtc.2015.7151580
|View full text |Cite
|
Sign up to set email alerts
|

An automatic thermal cycling based test platform for thermoelectric generator testing

Abstract: Abstract-Thermoelectric (TE) modules are solid-state devices that convert directly thermal energy in electrical energy. However, they can undergo performance degradation due to thermal cycling. In the present study, a control-based test platform that is capable to apply specific thermal cycling pattern at periodic intervals is presented in order to evaluate performance degradation that influence the TE module lifetime. Using this test platform, some parameters and the figure of merit ZT of a commercial TE modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…Another interesting setup is proposed in [27], where both the heat produced by an electrical resistance and the cooling capacity provided by a TEM, are controlled by a proportional-integral controller. Other propose the use of one or two opportunely driven auxiliary TEMs to set the temperature gradient on the TEM under test [2,28,33]. For example, in [28], ΘIN is obtained measuring only one heat flux induced into an aluminum block with a known thermal conductivity, interposed between the module under test and an auxiliary TEM used to set the average temperature, hence requiring only three temperatures to be measured.…”
Section: State Of the Art And Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another interesting setup is proposed in [27], where both the heat produced by an electrical resistance and the cooling capacity provided by a TEM, are controlled by a proportional-integral controller. Other propose the use of one or two opportunely driven auxiliary TEMs to set the temperature gradient on the TEM under test [2,28,33]. For example, in [28], ΘIN is obtained measuring only one heat flux induced into an aluminum block with a known thermal conductivity, interposed between the module under test and an auxiliary TEM used to set the average temperature, hence requiring only three temperatures to be measured.…”
Section: State Of the Art And Proposed Methodsmentioning
confidence: 99%
“…In the first case the Seebeck effect is predominant to convert temperature gradient sans-serifΔT into electrical energy, whereas, in the second case, the dual effect—the Peltier effect—is exploited. TEMs’ several positive features make them reliable [1,2], and thus their use is appealing for both academic and industrial researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emulation platform was firstly proposed in [ 24 ], the diagram and the physical structure of the platform is shown in Figure 2 and Figure 3 , respectively. This platform features a symmetrical structure composed by two fans, two modules (TEC and TEC ), acting as thermoelectric coolers (TEC), and a module acting as a thermoelectric generator (the TEG-under-test or just TEG).…”
Section: Proposed Systemmentioning
confidence: 99%
“…The authors concluded that the degradation of the TEG was mostly due to the degradation of the thermal contact. Unlike many of the studies mentioned above, the experimental rigs constructed by de Cerqueira Veras et al [18] and Tenorio et al [19] can vary the temperature on both sides of the TEG, which, according to the authors, enables the evaluation of TEGs under more realistic operational conditions. The test platform consists of a TEG positioned between two other thermoelectric modules acting as heater and cooler periodically.…”
Section: Introductionmentioning
confidence: 99%